Study of Rescheduling of MV Alfa Trans Satu Ship Repair Using Critical Path Method (CPM) and Project Evaluation and Review Technique (PERT) - Parlindungan Manik; Rika Afrodiyanti; Muhammad Luqman Hakim (International Journal of Marine Engineering Innovation and Research, 2023)
The ship repair project must work according to the schedule agreed in the work contract. However, in the process there are often delays between the initial plan and work in the field. The scheduling method is one of the influences on the success of repairs in order to produce efficient scheduling and cost planning. Based on these conditions, this study aims to obtain a new duration and the most optimal cost of crashing through an alternative, namely additional working hours (overtime hours) and additional workforce in the MV Alfa Trans Satu Ship repair project by applying the CPM and PERT methods. Based on the crash duration calculation using the CPM, the most effective and efficient alternative that can be used to accelerate the MV Alfa Trans Satu Ship repair project is by adding a workforce of 32 Person (an increase of 30% from the initial workforce). This acceleration alternative produces a duration below the normal duration, 21 days from the initial 25 days. The probability of success for this project using the PERT method can be completed within 21 days of 98.46%. The percentage increase in costs is only 4% of the normal for critical work, IDR 50,800,000.